Durian Agribusiness Development Strategy in Boven Digoel Regency - Dadan Moh Ramdan; Ma'mun Sarma; Adi Hadianto (Jurnal Penelitian Pendidikan IPA, 2024)
The agricultural sector, which includes forestry, fisheries, animal husbandry, hunting, and farming services, is the main contributor to forming Boven Digoel Regency's GRDP. The largest commodity contributing to GRDP comes from the plantation crop subsector, not the horticulture subsector, such as durian, even though the subsector has considerable production potential. This is due to suboptimal post-harvest management and limited knowledge of durian cultivation technology among local farmers. Most farmers still use less efficient traditional methods, so the yield could be more optimal. This study aims to analyze internal and external factors and formulate local economic development strategies based on durian agribusiness. The data used included primary and secondary data, and the analysis was conducted using descriptive methods, IFE, EFE, IE Matrix, SWOT Analysis, and QSPM. The results showed that the durian agribusiness economy in Boven Digoel Regency based on the IE matrix is in quadrant I (growth and investment) with internal factors 3.13 and external factors 3.08. SWOT analysis resulted in three main strategies: market expansion, diversification of durian processed products, and restructuring the production system. Diversification of processed products, such as dodol and ice cream, proved to be the most effective strategy based on QSPM analysis, with a score of 6.32.